Accidentabilidad y salud laboral en la empresa Conversa del cantón Sangolquí. Propuesta de un sistema de seguridad y prevención de riesgos laborales durante el período 2013-2014. - Viteri Medina, Galo Alejandro (2015)
The inability of applying an specific Security and risks prevention system at CONVERSA, makes that workers and all the people involved in the productive process do not know properly all the norms and legal rules that have to be followed during their working hours, so that, there is a lack of control in those processes. The purpose of having done this research is to find and define all the risks conditions that could threaten workers during the development of different processes inside the factory, as well as, propose a solution that help the company and people who work there to improve their performance in their compulsory duties and therefore we can have better results in labor, social, productive and economic fields.